Efficacy of Low Dose Magnesium Sulphate in Control of Convulsion in Eclampsia in a Tertiary Care Hospital of Bangladesh (Eastern Medical College Journal, 2024)
Background: Eclampsia is the third major cause of maternal mortality in our country. Global studies have demonstrated that using magnesium sulphate (MgSO4) to manage hypertensive disease in pregnancy reduces morbidity and mortality due to severe pre-eclampsia and eclampsia. Magnesium sulphate is therefore the anticonvulsant of choice for both prevention and treatment of eclampsia. The aim of the study is to evaluate the use and efficacy of a low dose (6 gm) of magnesium sulphate in controlling convulsion amongst women with pre-eclampsia and eclampsia in a tertiary care hospital of Bangladesh.Material and Methods: This comparative interventional study was conducted in Sylhet MAG Osmani Medical College and Hospitalwith ethical clearance from respective IERB. Hundreds (100) eclampsia patients have been selected by consecutive sampling from the eclampsia ward and divided into 2 groups by random selection. Group A contains 50 patients who received a low dose and group B also contains 50 patients who received a loading plus a maintenance dose of MgSO4. Patient’s demographic data and follow up signs were recorded in a data collection sheet. Data was coded and entered SPSS for analysis.Results: Among 100 patients, the mean age of the participants for group A and group B was 23.98 ±5.26 and 23.92±3.85 years, respectively. The mean gestational age was 37.38±2.88 weeks for Group A and 36.94±3.13 weeks for Group B. Occurrence of eclampsia was found to be significantly high (Group A 58% and Group B 78%) among primigravida of both groups, belonged to low (Group A 60% and Group B 50%) and middle (Group A 36% and Group B 46%) socioeconomic backgrounds. Received antenatal care irregularly (only one visit) (Group A 52% and Group B 48%). Antepartum eclampsia was 90% in Group A and 86% in Group B, intrapartum was 2% in Group B and postpartum was 10% in Group A and 12% in Group B. Recurrence of convulsion was only observed in 8% of women from Group A and 10 % from Group B. Maternal complications were seen in only 2% woman from each group.Conclusion: This study revealed that a low dose regimen can control convulsions much more effectively than a conventional full dose regimen. The recurrence rate of convulsion was not significant with this low dose and has the advantage of lower magnesium toxicities. It is also cost-effective.Eastern Med Coll J. July 2024; 9 (2): 115-120